Multiple Oscillations and Phase Locking in Human Gamma Responses: An Essay in Search of Eigenvalues - BAŞAR, EROL (Anka Publisher, 116-11 Sok No.10 K 2 D 2, Bornova, Izmir 35050, Turkey, 2012)
This report describes a new strategy to analyze and interpret the fine structure of the human brain's gamma oscillations between the frequency ranges of 28 to 48 Hz. There are at least 3-4 phase/time-locked gamma responses within the 28-45-Hz frequency window. Late responses starting around 300 ms are probably responses that are conveyed over reticular formation, hippocampus, etc., whereas the early response in the primary occipital cortex O1 starting at 100 ms is most probably the direct response over the short pathway over lateral geniculate nucleus. Eigenvalues or nodes: It is remarkable that nodes or Eigenvalues are observed, despite the complexity of the pathways and the superposition of several oscillations. It appears that the event-related oscillations in the gamma band undergo an increasing frequency modulation. The time course in the first 200 ms has lower frequencies of approximately 28-30 Hz. With increasing time, the frequencies of these oscillations reach values of up to 46 Hz. The brain reacts within three-to-four frequency bands, depending on the modality of stimulation. In the context of quantum dynamics, the results are tentatively explained via the concept of eigenvalues.
Keywords: Auditory Oddball Paradigm; Cat Visual-Cortex; Evoked-Potentials; Reticular-Formation; Electrical Signals; Olfactory Bulb; Alpha-Activity; Band Activity; Eeg-Activity; Brain; Oscillation; Phase Locking; Human Gamma Responses; Eigenvalues; İşitsel Oddball Paradigması; Kedi Görsel-Korteks; Uyarılmış-Potansiyeller; Retiküler Oluşumu; Elektrik Sinyalleri; Koku Ampulü; Alfa-Aktivitesi; Bant Etkinliği; EEG Faaliyetini; Beyin; Salınım; Faz Kilitleme; İnsan Gamma Tepkileri; Özdeğerler